Reframing the “Universality” of International Law in a Globalizing World - al Attar, Mohsen (McGill Law Journal / Revue de droit de McGill, 2013)
In this essay, I highlight the historical use of notions of universality and objectivity in international law to advance First World economic interests, primarily through the codification of conditions that sustain ongoing Third World dispossession. I argue that these interests have taken on a transnational character and are being pursued through an elaborate network of meta-regulatory regimes beneficial to an emergent transnational capitalist class. These regimes are used to diffuse neoliberal economic reform on a global scale, resulting in the embedding of various neoliberal precepts both in legal machinery and in social meaning. Finally, I suggest that while instances of resistance are observable, critical international legal jurists appear ambivalent in their efforts at crafting proposals for reform of the global legal order. While some champion a type of global legal pluralism that would recognize the legitimacy of lawmaking as executed by non-institutional actors, many remain perplexed as to how we might reconcile the pursuit of a universally and objectively just order in a pluralist, subjective, and highly stratified world. I conclude by applying Nancy Fraser’s “political dimension of justice” to conceptualize and structure more representative participatory transnational lawmaking processes, the kind that would promote both parity of participation and actor subjectivity, and possibly further the cause of global justice.